Inhibition of Gliocladium sp against plant pathogenic fungus and their exoenzyme activity - Fardhani, Dinar Mindrati; Fuadiyah, Dzakiya Alda; Susila, Wisnu Adhi; Nugraheni, Ika Afifah (Universitas 'Aisyiyah Yogyakarta, 2024)
Gliocladium sp. It is known to have an antagonistic mechanism against other organisms by means of hyper parasitism, antibiosis and lysis, as well as competition. This study aims to determine the effectiveness of Gliocladium sp. in inhibiting several types of plant pathogenic fungi and their exoenzyme activity. Inhibition testing was carried out by the Dual Culture Assay method on several plant pathogenic fungi including Colletotrichum gloeosporioides, Rhizoctonia solani, Fusarium sp., and Phytophthora sp. The exoenzyme activity tested includes cellulolytic tests, amylolytic tests, and chitinolytic tests. Antagonist testing showed that Gliocladium sp. able to inhibit the growth of all pathogenic fungi tested with varying percentage of inhibition. High percentage of inhibition was shown in the pathogens Colletotrichum gloeosporioides and Rhizoctonia solani with percentages of 78.75% and 75%, respectively. Then, the antagonist activity against Fusarium sp. has a moderate resistance percentage of 56%. Meanwhile, a low percentage of inhibition is shown in Gliocladium sp. against Phytophthora sp. with a figure of 25%. From the characterization of exoenzyme activity in Gliocladium sp., negative results were obtained in liquid and solid Carboxymethyl Cellulose, amylum, and chitin media. Meanwhile, in the amylolytic test, positive growth was marked by the appearance of mycelia on the surface of the amylum liquid medium, but in the solid media negative results were obtained against the amylase enzyme. Gliocladium sp fungus has the potential to be a biocontrol agent against various plant pathogenic fungi